When gender matters: the role of women in mergers and acquisitions - Tiveron, Benedetta; Mantovani, Guido Max; Moro, Andrea (Virtus Interpress, 2023)
The paper investigates the impact that female directors have on mergers and acquisitions (M&A) deals’ initiation with a negative binomial regression analysis on 250 companies in Europe in the decade 2009–2018. Results show that the addition of a female director increases the number of bid initiations by 12.86 percent, an outcome in contrast with the extant literature, according to which female presence would decrease the number of acquisitions to mitigate male CEO overconfidence (Levi et al., 2014). Moreover, after introducing an interaction term between female share on boards and the single countries, it was found that the magnitude and sign of female impact on firms’ acquisitive behavior vary according to the nation in which the firm is located. Results indicate that female directors bring relevant changes in boardroom’s dynamics, which are then reflected in the company’s M&A activity.
Keywords: Board of Directors; Female Directors; Gender Equality